2020
DOI: 10.1155/2020/3912931
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Massage Reduces Visceral Hypersensitivity via Regulating GDNF and PI3K/AKT Signal Pathway in a Rat Model of Irritable Bowel Syndrome

Abstract: Changes in gut motility and visceral hypersensitivity are two major features of irritable bowel syndrome (IBS). Current drug treatments are often poorly efficacious, with many side effects for patients with IBS. Complementary therapies, such as acupuncture or abdominal massage, have received more attention in recent years. In this study, a rat model of IBS with diarrhea (IBS-D) was established by instillation of acetic acid from the colon. The effects of abdominal massage on changes in gut motility, visceral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
7
1
Order By: Relevance
“…Current studies have shown that anti-TNF drugs can be used to exert anti-inflammatory effects, thereby effectively treating inflammatory bowel disease ( 35 , 36 ); however, few studies have proven that drugs act directly through TNF signaling pathways. Conversely, the PI3K–Akt signaling pathway is directly related to stress-induced UC and irritable bowel syndrome (IBS) ( 37 , 38 ). The PI3K–Akt signaling pathway is reportedly related to various diverse physiological stresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current studies have shown that anti-TNF drugs can be used to exert anti-inflammatory effects, thereby effectively treating inflammatory bowel disease ( 35 , 36 ); however, few studies have proven that drugs act directly through TNF signaling pathways. Conversely, the PI3K–Akt signaling pathway is directly related to stress-induced UC and irritable bowel syndrome (IBS) ( 37 , 38 ). The PI3K–Akt signaling pathway is reportedly related to various diverse physiological stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K–Akt signaling pathway is reportedly related to various diverse physiological stresses. It plays a crucial regulatory role during cellular stress ( 39 41 ) and is reportedly associated with stress-induced diarrhea, predominantly IBS (IBS-D), and UC ( 38 , 42 44 ). In addition, the results of KEGG enrichment analysis show that the PI3K–Akt signaling pathway (number of enriched genes = 39) can enrich more genes than the TNF signaling pathway (number of enriched genes = 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder with persistent or recurrent episodes of intestinal disorder [ 1 ]. It is characterized by abdominal pain, abdominal distension, altered bowel habits, and/or character of stool that severely affect the quality of patients' life [ 2 ]. A wide spectrum of clinical manifestations and a lack of a specific diagnostic basis [ 2 ] make it difficult to treat.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by abdominal pain, abdominal distension, altered bowel habits, and/or character of stool that severely affect the quality of patients' life [ 2 ]. A wide spectrum of clinical manifestations and a lack of a specific diagnostic basis [ 2 ] make it difficult to treat. Although medication, nutritional support, and psychotherapy are currently in use, few drugs are available for effective treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%